The Effects of Huanglongbing on Florida Oranges - Tripti Vashisth; Yu Wang; Michelle Danyluk; Renée M. Goodrich-Schneider; Charlie Sims; Jamie D Burrow (EDIS)
Minor revision: https://edis.ifas.ufl.edu/fs169